PERTIWI DAN TIRTA MENGUKUHKAN KEMBALI NILAI TRI HITA KARANA DI BANJAR NEGARI DESA SINGAPADU TENGAH - Kadek Putri Oktaviana Melani; Pande Komang Lisa Tamara Sandi; I Putu Gede Putra Setiawan; I Gusti Lanang Raiditya Agung; Achmad Faisal Ramdani; I Made Mahardhika; Putu Agus Permanamiarta (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2026)
Thematic Community Service Program (KKN) is a form of community service aimed at encouraging community empowerment through the application of knowledge and local wisdom. This activity was conducted in Banjar Negari, Singapadu Tengah Village, Sukawati District, Gianyar Regency, from February 18–March 12, 2026, by 14 students from the University of PGRI Mahadewa Indonesia (UPMI). The program, themed "Pertiwi and Tirta Reaffirm the Values ​​of Tri Hita Karana," was implemented through five main work programs: environmental conservation through the distribution of tree seedlings and the release of fish seeds, the "Creative Active Saturday" program for elementary school students, elderly exercise and laughter yoga activities, mentoring for arts and culture parades and Balinese Language Month, and supporting the implementation of Integrated Health Posts (Posyandu). The method used was a participatory approach through stages of socialization, mentoring, program implementation, and evaluation. The results of the activities showed an increase in public awareness of environmental conservation, health, education, and local culture. Furthermore, the program successfully strengthened the implementation of the Tri Hita Karana values, encompassing Parahyangan, Pawongan, and Palemahan, as the foundation for harmonious and sustainable community development.